The effect of toolkits usage and ideation community contest on innovation: the mediating role of relationship quality / Ripan Kumar Saha ... [et al.] - Saha, Ripan Kumar; Lian Seng, Tey; Taha, Azni Zarina; Garib Singh, Sharan Kaur (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Limited studies have focused on how social media activies can contribute to organizational innovation. The purpose of this research is to investigate the impacts of toolkits usage and ideation community contest on innovation in the context of social media. Additionally, this study aims to narrow the gap by examining the intervening function of relationship quality amongst the two dimensions of social media activities and innovation respectively. Employing a sample of 393 manufacturing firms in Malaysia, our findings confirm that the toolkits usage and ideation community contest components of social media activities are positively correlated with innovation. Additionally, the findings found that relationship quality performs a mediating impact on social media activities and innovation. The study concluded with arguments concerning social media activities and its correlation to innovation transcend national boundaries. Based on the findings, several innovation strategies were put forward for Malaysian manufacturing firms.